Unintentional injury mortality in India, 2005 – estimates from a nationally representative mortality survey of 1.1 million homes. (1st March 2011) - Jagnoor, J; Keay, L; Ivers, R; Suraweera, W; Jha, P
Abstract : Background: Studies have suggested considerable injury mortality in India, a large proportion of these is due to unintentional injuries. However no reliable data are available to provide national estimates for these deaths. Objective: To determine the mortality burden of unintentional injuries at a national level. Methods: We analysed unintentional injury data from the Sample Registration System – Million death study from 2001 to 2003, using verbal autopsy method, in a nationally representative sample of over 125 000 deaths among 1.1 million homes. Findings: Unintentional injuries (ICD-10 codes for Chapter XX) were identified and contributed 7% to all cause mortality. Proportionate mortality was highest in the age group of 70+ years, with more than 60% injury deaths due to falls, although there is also greater misclassification of causes at older ages. The highest proportions of drowning deaths were in under 5 years (14%), the highest proportion of road traffics deaths were in the age group of 30–39 years (10%) of all unintentional deaths. Proportionate mortality due to unintentional injury in males (8%) was higher than in females (5%). Overall there was no difference in rural urban proportionate mortality, though type of injury leading to deaths differed. Road traffic injuries (29%), falls (26%) and drowning (11%) were the leading causes of injury mortality. Interpretation: Unintentional injury burden in India is substantial. There is need for continued monitoring of injury mortality and understanding of specific risk factors for development of effective injury prevention programs.